Análisis de la sostenibilidad financiera del seguro de salud y seguro de pensiones del Instituto Ecuatoriano de Seguridad Social durante el periodo (2018-2022). - Mendieta Riofrio, Ana Paula; Merizalde Cajamarca, Anthony Eduardo (Machala : Universidad Técnica de Machala, 2024)
The financial sustainability of the health insurance and pension programs of the Ecuadorian Social Security Institute is a major challenge. The entity is facing a growing demand for medical services in the health insurance area due to the aging of the population and the need to cover increasingly expensive medical treatments and technologies. Due to this situation, the financial resources of the IESS must be managed in an efficient and sustainable manner to ensure continuity and quality of medical care for its affiliates. To improve the long-term financial viability of the IESS health insurance system, it is essential to implement measures to control spending, improve resource management and seek additional sources of financing. As for the pension system, the increasing longevity of the population, the declining birth rate and economic fluctuations also jeopardize the financial sustainability of the IESS. Structural reforms that promote efficiency in the management of pension funds, encourage formal employment and help increase the contributor base are necessary to ensure the viability of the pension system. It is also important to consider cautious and diversified investment strategies that generate long-term returns. To guarantee the financial sustainability of the IESS pension system in the future, it is essential to promote financial education and awareness of the importance of social security.
La sostenibilidad financiera de los programas de seguro de salud y pensiones del Instituto Ecuatoriano de Seguridad Social es un desafío importante. La entidad se enfrenta a una creciente demanda de servicios médicos en el ámbito del seguro de salud debido al envejecimiento de la población y a la necesidad de cubrir tratamientos y tecnologías médicas cada vez más costosas. Los recursos financieros del IESS deben administrarse de manera eficiente y sostenible para garantizar la continuidad y calidad de la atención médica para sus afiliados debido a esta situación. Para mejorar la viabilidad financiera a largo plazo del seguro de salud del IESS, es fundamental implementar medidas de control del gasto, mejorar la gestión de los recursos y buscar fuentes de financiamiento adicionales. En cuanto al sistema de pensiones, el aumento de la longevidad de la población, la disminución de la tasa de natalidad y las fluctuaciones económicas también ponen en peligro la sostenibilidad financiera del IESS. Es necesario llevar a cabo reformas estructurales que fomenten la eficiencia en la gestión de los fondos de pensiones, fomenten el empleo formal y contribuyan a aumentar la base de cotizantes para asegurar la viabilidad del sistema de pensiones. Es importante considerar también estrategias de inversión cautelosas y diversificadas que generen ganancias a largo plazo. Para garantizar la sostenibilidad financiera del sistema de pensiones del IESS en el futuro, es esencial promover la educación financiera y la concientización sobre la importancia de la previsión social.
Keywords: SOSTENIBILIDAD; PENSIONES; SALUD; IESS